John Steinbeck stands with three unidentified men. - unknown:::creator:::::::::::: (Sag Harbor, New York; USA, 2022)
John Steinbeck stands with three unidentified men, possible at the Old Whalers Festival. Steinbeck is wearing British navy cap and yachting jacket with Pigasus emblem visible. Original in safe.